An analytical model for sensing microvascular blood flow in flaps and organ grafts. (January 2023) - Li, Shupeng; Lu, Di; Pet, Mitchell; Rogers, John A.; Huang, Yonggang
Abstract: Thrombosis after free flap transfer or solid organ allotransplantation surgeries can lead to flap or organ failure requiring re-transplantation and sometimes leading to death. Current technologies can provide early warnings of thrombosis, but the resulting measurements can be influenced by motions associated with route operations in patient care and by subtle aspects associated with the use of the devices. These systems also require wired interfaces to external data acquisition hardware, which limits patient mobility and subject the sensor to artefact from interface disruption attributable to external tension. Furthermore, many existing systems require that the probe be mounted directly on the anastomosed artery or vein which puts these delicate structures at risk for kinking, avulsion, or other disruption. Recent reports describe a wireless, implantable flow sensing probe technology that exploits thermal transport mechanisms to enable continuous monitoring of microvascular flow velocity within peripheral tissue that is remote from the critical blood supply. The capability is useful for the reliable detection of thrombosis in auto- or allotransplanted flaps or organs. Because the probe directly measures temperature rather than flow velocity, analytical models must be used to interpret the results. Here, such a model, accounting for both heat conduction and heat convection (due to blood flow), is developed to determine the blood flow velocity in flaps and organ grafts for this flow sensing probe. The model is validated by in vitro experiments without and with blood flow and further applied to in vivo experiments to predict the flow velocity. The model serves as an important support for this type of flow sensing probe and ensures reliable and accurate flow monitoring after the transplantation operations.